2021
DOI: 10.1108/rpj-08-2020-0186
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of customized tubular scaffolds for tracheal tissue engineering by using solvent based 3D printing on predefined template

Abstract: Purpose This paper aims to discuss the successful fabrication of customized tubular scaffolds for tracheal tissue engineering with a novel route using solvent-based extrusion 3D printing. Design/methodology/approach The manufacturing approach involved extrusion of polymeric ink over a rotating predefined pattern to construct customized tubular structure of polycaprolactone (PCL) and polyurethane (PU). Dimensional deviation in thickness of scaffolds were calculated for various layer thicknesses of 3D printing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The polymeric scaffolds of PCL, PCL/PU and PU, post drying in a vacuum oven at 50°C for 48 h, showed no toxicity during the in vitro study (MTS assay for 21 days) that can be found in the authors' previous research work. 18 It indicated that the possibility of the toxic residual present in the samples was insignificant, though the measurement of solvent residual was not performed in the present work.…”
Section: Fabrication Of Tubular Scaffoldsmentioning
confidence: 78%
See 1 more Smart Citation
“…The polymeric scaffolds of PCL, PCL/PU and PU, post drying in a vacuum oven at 50°C for 48 h, showed no toxicity during the in vitro study (MTS assay for 21 days) that can be found in the authors' previous research work. 18 It indicated that the possibility of the toxic residual present in the samples was insignificant, though the measurement of solvent residual was not performed in the present work.…”
Section: Fabrication Of Tubular Scaffoldsmentioning
confidence: 78%
“…The 3D printer worked on an indigenous algorithm which allowed the extruder to extrude over a rotating template making an axisymmetric part. 18 It included a syringe plunger arrangement which was operated by three motors namely M1, M2 and M3.…”
Section: Polycaprolactonementioning
confidence: 99%
“…The hemolysis ratio of scaffolds was less than 2%, which demonstrated their good hemocompatibility. [ 24 ] To further discern the biocompatibility of the scaffolds, the cell seeding efficiency was determined, which was found to be 82.5 ± 1.7%, 92.2 ± 3.4%, and 96.1 ± 1.9% for TSF0.5, TSF1.0, and TSF1.5 scaffolds, respectively (Figure 7b). The tracheal scaffolds showed higher numbers of cells than that of the SF aerogels, which may be ascribed to their 3D porous structure conducive for cell proliferation and adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…While tissue‐engineered tracheal scaffolds possess great potential for the replacement of defected tracheal tissues, fabricating a suitable tracheal candidate mimicking the NT structurally and functionally still faces numerous challenges. [ 3,24 ] Fabrication techniques, such as electrospinning and 3D printing can be exploited to fabricate tracheal scaffolds. [ 25 ] However, tracheal scaffolds fabricated from each of these techniques face several limitations; electrospun nanofibers exhibit compact structure, which may impede the diffusion of nutrients and oxygen as well as the infiltration of cellular components and tissues into scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation